2005
DOI: 10.1007/s00439-005-0072-2
|View full text |Cite
|
Sign up to set email alerts
|

Disruptions of the novel KIAA1202 gene are associated with X-linked mental retardation

Abstract: The extensive heterogeneity underlying the genetic component of mental retardation (MR) is the main cause for our limited understanding of the aetiology of this highly prevalent condition. Hence we set out to identify genes involved in MR. We investigated the breakpoints of two balanced X;autosome translocations in two unrelated female patients with mild/moderate MR and found that the Xp11.2 breakpoints disrupt the novel human KIAA1202 (hKIAA1202) gene in both cases. We also identified a missense exchange in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(69 citation statements)
references
References 30 publications
(32 reference statements)
4
65
0
Order By: Relevance
“…Most adult tissues examined express Shrm4. This agrees with previous data showing that Shrm4 mRNA is present in many adult and embryonic tissues [Hagens et al, 2005]. In brain, our Shrm4-specific antibodies reproducibly detect a protein with an apparent molecular mass of 90 kDa (Fig.…”
Section: Cloning and Characterization Of Mouse Shroom4supporting
confidence: 93%
See 2 more Smart Citations
“…Most adult tissues examined express Shrm4. This agrees with previous data showing that Shrm4 mRNA is present in many adult and embryonic tissues [Hagens et al, 2005]. In brain, our Shrm4-specific antibodies reproducibly detect a protein with an apparent molecular mass of 90 kDa (Fig.…”
Section: Cloning and Characterization Of Mouse Shroom4supporting
confidence: 93%
“…This paper describes the characterization of Shrm4, a member of the Shroom-family of genes and the mouse ortholog of human SHRM4, a gene implicated in Xlinked mental retardation in humans [Hagens et al, 2005]. As would be expected, the predicted mShrm4 protein is highly similar to hShrm4, exhibiting approximately 80% overall sequence identity, although this percentage is significantly higher in the PDZ and ASD2 motifs.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…A missense exchange of SHROOM4 was reported to segregate with Stocco dos Santos XLMR syndrome (OMIM 300434) in a large fourgeneration pedigree. 21 The affected males in the reported family presented with severe MR, delayed or no speech, seizures and hyperactivity. Our patient with null SHROOM4 showed only moderate MR, suggesting that the missense exchange detected in Stocco dos Santos XLMR syndrome contributes to the pathogenesis of MR together with other phenotypes in a gain-of-function manner.…”
Section: Cnvs In Xlmr S Honda Et Almentioning
confidence: 96%
“…Information from the UCSC genome browser revealed that the deleted region contains SHROOM4 (OMIM 300579), reported to be a causative gene for XLMR. 21 Sample of his mother (II-4) was not available. The highdensity oligonucleotide aCGH revealed that the deletion at Xp11.22 in family MR67H was also flanked distally by a sequence gap and proximally by a complex repeat-rich locus containing SSX families (SSX7 and SSX2), melanoma antigen (MAGE) families and X-antigen (XAGE) families (Figure 4).…”
Section: Mr67hmentioning
confidence: 99%